Enhanced antitumor effects of BPD-MA-mediated photodynamic therapy combined with adriamycin on breast cancer in mice - Tong Zhong-sheng; Miao Pei-tian; Liu Ting-ting; Jia Yong-sheng; Liu Xiao-dong (Acta Pharmacologica Sinica, 2016)
Aim: Photodynamic therapy (PDT) is an emerging treatment used to eradicate premalignant and early-stage cancers and to reduce tumor size in end-stage cancers. In this study, we investigated the effects of a combination of benzoporphyrin derivative monoacid ring A (BPD-MA)-mediated PDT with adriamycin (ADM) on 4T1 breast carcinoma cells in vivo and the mechanisms underlying this effect. Methods: Normal BALA/c female mice bearing 4T1 breast carcinoma xenografts were tested. The animals were treated with PDT (BPD-MA 1 mg/kg, iv, plus single-dose laser irradiation) or ADM (5 mg/kg, iv) alone, or a combination of PDT with ADM. The tumor growth rate was determined by measuring the tumor weight. Cell apoptosis was measured with flow cytometry, and the expression of apoptosis-related molecules was assessed using Western blot. Microvessel density (MVD) was determined with immunohistochemical staining. Results: Compared to PDT or ADM alone, PDT plus ADM produced a combined inhibition on the tumor growth, prolonged life span, and enhanced apoptosis in the mice bearing 4T1 subcutaneously xenografted tumors. The combination of PDT and ADM exerted additive effects on the upregulation of Bax and the downregulation of Bcl-2, and on the reduction of MVD in 4T1 xenografted tumors. Conclusion: Our results demonstrate that PDT plus ADM exerts enhanced in vivo antitumor effect on breast cancer, which is closely associated with the cooperative regulation of extrinsic apoptotic pathways and the inhibition of tumor angiogenesis. Thus, PDT plus ADM is a promising combined treatment strategy for breast carcinoma.